Negara dalam Narasi: Analisis Framing Politik LKBN ANTARA terhadap Pemerintahan Prabowo-Gibran Dibandingkan Kompas.com - Endika Fitra Wijaya; Reza Alerio Reihan; Adiba Nurkhafiza; Yulianti Harmonis (Jurnal Humanitaria Jurnal Ilmu Sosial dan Humaniora, 2024)
This research analyzes the framing patterns of political news coverage by the Indonesian state news agency, LKBN ANTARA, in reporting on the Prabowo-Gibran administration, and compares it with the framing used by private media, Kompas.com. The study is motivated by ANTARA’s position as an official state news agency, which holds a potential structural bias when reporting on the ruling government. This research employs a qualitative approach using Robert N. Entman’s framing analysis method, comprising four elements: problem definition, causal interpretation, moral evaluation, and treatment recommendation. Data were collected from online news reports published by ANTARA and Kompas.com between October 2024 and April 2025. The findings reveal that ANTARA tends to frame news affirmatively toward the government, emphasizing optimism and successful programs while providing minimal space for critical voices. In contrast, Kompas.com demonstrates a more pluralistic framing pattern, offering space for public criticism and expert analyses of government policies. This difference in framing significantly impacts the construction of public reality, where a single narrative from state media risks narrowing public discourse and reducing political literacy among the population. This research is one of the initial studies specifically examining the framing practices of state media regarding the Prabowo-Gibran administration and contributes to the development of political communication studies in Indonesia. Keywords: Framing, ANTARA, Prabowo-Gibran, Political Media, Political Communication